A study on cervical cancer screening using pap smear in urban area in state of Meghalaya, India - Mishra, Priti; Thapa, Ragini; Dinkar, Arvind Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cancer cervix is fourth most common cancer in world second most common in India. The objective of the study is to identify abnormal pap smear cytology in women undergoing the test. Methods: This retrospective study conducted in 200 women attending gynae OPD of Military Hospital, Shillong, Meghalaya, India between January 2016 to December 2017. Pap smear test was done, and classification was done as per Bethesda system 2014. Results: 105 women had normal cytology findings and 23 had abnormal cytology. Conclusions: Cervical cancer is the most common cancer for which screening is done. If pap smear is done every 3 years as per the guidelines mortality due to cervical cancer can be reduced. Every woman should undergo pap test at least once in her life before the age of 45 years. Timely screening of preinvasive lesion allows prevention from invasive cervical cancer.